On the concavity of some functions connected with the two-dimensional normal distribution - Bodin, N.; Zalgaller, V. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Н. А. Бодин, В. А. Залгаллер. Вогнутость некоторых функций, связанных с двумерных нормальным распределениемN. Bodin, V. Zalgaller. Kai kurių funkcijų, susijusių su dvimačiu normaliniu pasiskirstymu, įgaubtumas